Circulating Nitrite and Nitrate are Associated with Job-Related Fatigue in Women, but not in Men - Takaki, Jiro (MDPI, 2013)
A recent study indicated that serum nitrite and nitrate (NO(x)) is inversely associated with general fatigue. The purpose of this study was to confirm the negative association between nitric oxide (NO) and fatigue and to examine whether NO can prevent fatigue caused by job strain. The subjects, 570 workers (272 men and 298 women), answered self-administered questionnaires and underwent a medical examination. Job strain was measured using the Job Content Questionnaire. Fatigue was evaluated using the Profile of Mood States. Venous blood samples were collected after overnight fasting. Plasma NO(x) concentration was determined by the ozone-based chemiluminescence assay. Plasma NO(x) levels were significantly (p < 0.05) negatively associated with fatigue even after adjustment for job strain and potential confounders in women, but not in men. Significant (p < 0.05) interactions showed that, in women, as the level of the job strain worsened, fatigue was exacerbated, but the plasma NO(x) seemed to buffer the association, even after adjustment for potential confounders and the interaction between job strain and vegetable intake. In women, NO seemed to be inversely associated with fatigue and to buffer the association between job strain and fatigue, but not in men.